Photovoltaic module having film layer comprising hydrophilic fumed silica
By using compositions made of materials such as olefin-based polymers and hydrophilic smoky silica, the problem of low volume resistivity of the photovoltaic module sealant material is solved, and higher volume resistivity and better weather resistance are achieved, and module power loss caused by PID is prevented.
Patent Information
- Application Number
- CN202411163100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2019-03-29
- Publication Date
- 2025-03-04
AI Technical Summary
The volume resistivity (VR) of existing photovoltaic module sealant materials is low, resulting in poor potential induction degradation (PID) resistance performance, which in turn leads to module power loss.
A sealant film with improved volume resistivity is formed using a composition composed of an olefin-based polymer, hydrophilic fume silica, alkoxysilane, organic peroxide and crosslinking additive.
The volume resistivity of the sealant film is significantly improved, from 5.0*1017ohm.cm to 6.0*1018ohm.cm, effectively preventing module power loss caused by PID and improving the weather resistance of the sealant film.
Smart Images

Figure CN119552447A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application No. 201980095849.2 (filing date: March 29, 2019, invention name: photovoltaic module having a film layer including hydrophilic fumed silica) Technical Field
[0002] The present disclosure relates to olefin-based encapsulant films having improved volume resistivity and electronic devices, such as photovoltaic modules, containing such encapsulant films. Background Art
[0003] The construction of a typical electronic device, such as a photovoltaic (PV) module, typically includes a front light emitting and receiving layer, typically glass, followed by a front sealant film layer, electronic components (e.g., photovoltaic cells), a rear sealant film layer, and a final rear layer of a polymer backsheet or glass. In some cases, the rear sealant film layer and the backsheet can be a single film with integrated sealant and backsheet functionality, or a back encapsulant composite (BEC) film. Since photovoltaic modules are used outdoors, they must be weather-resistant, such as protecting the electronic components from moisture, shock, and vibration and providing electrical resistance. The sealant film provides insulation and environmental protection for electrical components used in electronic devices, such as photovoltaic cells used in PV modules.
[0004] Ethylene vinyl acetate (EVA) is currently widely used as a sealant material for PV cells due to its transparency, flexibility and easy conversion into cross-linkable sheets. However, EVA has poor weather resistance and high polarity, resulting in low volume resistivity (VR). VR is important because it affects potential induced degradation (PID) resistance performance. Sealed solar cells with low VR sealant materials may result in significant module power losses due to PID.
[0005] Olefin-based sealants, such as ethylene / α-olefin copolymers, also have excellent transparency, heat resistance, and can be easily converted into cross-linkable films. Although olefin-based sealants generally have improved VR compared to EVA, the VR range of olefin-based sealants is wide, with VR greater than 10. 17 Olefin-based seals with a VR of ohm.cm achieve the best PID prevention performance. Olefin-based seals with lower VR will benefit from improvements in VR.
[0006] There is a need for sealant films containing olefin-based resins having improved volume resistivity. Summary of the invention
[0007] According to an embodiment of the present disclosure, a composition is provided. The composition comprises (A) a volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymer; (B) hydrophilic fumed silica; (C) alkoxysilane; (D) organic peroxide; and (E) from 0 wt % to 1.5 wt % of a cross-linking aid.
[0008] According to a further embodiment of the present disclosure, a film layer is provided. The film layer is made of a composition comprising: (A) a volume resistivity greater than 5.0*10 15 ohm.cm of an olefin-based polymer; (B) hydrophilic fumed silica; (C) an alkoxysilane; (D) an organic peroxide; and (E) from 0 wt % to 1.5 wt % of a crosslinking aid, wherein the volume resistivity of the film layer is from 5.0*10 17 ohm.cm to 6.0*10 18 ohm.cm.
[0009] According to a further embodiment of the present disclosure, a photovoltaic module is provided. The photovoltaic module comprises a photovoltaic cell and a film layer composed of a composition, wherein the composition is a reaction product of a composition comprising: (A) a volume resistivity greater than 5.0*10 15 ohm.cm of an olefin-based polymer; (B) hydrophilic fumed silica; (C) an alkoxysilane; (D) an organic peroxide; and (E) from 0 wt % to 1.5 wt % of a crosslinking aid, wherein the volume resistivity of the film layer is from 5.0*10 17 ohm.cm to 6.0*10 18 ohm.cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is an exploded perspective view of a photovoltaic module according to an embodiment of the present disclosure.
[0011] definition
[0012] Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, the contents of any referenced patent, patent application, or publication are incorporated by reference in their entirety (or their equivalent U.S. versions are so incorporated by reference), especially with respect to definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and common general knowledge in the art.
[0013] The numerical ranges disclosed herein include all values from the lower limit to the upper limit and include the lower limit and the upper limit. For ranges containing explicit values (e.g., a range of 1 or 2 or 3 to 5 or 6 or 7), any subrange between any two explicit values is included (e.g., the above range 1-7 includes all subranges 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).
[0014] An "alpha-olefin" is a hydrocarbon molecule that includes (i) only one olefinic unsaturation, the unsaturation being located between the first and second carbon atoms, and (ii) from 2 or 3, or from 4 to 5, or 8, or 10, or 20 carbon atoms. Non-limiting examples of alpha-olefins for preparing elastomers include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-dodecene, and mixtures of two or more of these monomers.
[0015] A "blend" or "polymer blend" is a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined by transmission electron spectroscopy, light scattering, x-ray scattering, and any other method known in the art.
[0016] A "composition" or "formulation" is a mixture or blend of two or more components. In the case of a mixture or blend of materials used to make an article, the composition includes all of the components in the mixture, e.g., polymers, catalysts, and any other additives or agents, such as curing catalysts, antioxidants, flame retardants, etc.
[0017] Whether specifically disclosed or not, the terms "comprises," "comprising," "having," and similar terms are not intended to exclude the presence of any additional components, steps, or procedures. Unless stated to the contrary, all methods claimed by using "comprising" may include one or more additional steps, equipment parts or components, and / or materials. In contrast, the term "consisting essentially of" excludes any other components, steps, or procedures from the scope of any subsequent enumeration, except those that are not essential for operability. The term "consisting of" excludes any components, steps, or procedures that are not specifically described or listed. Unless otherwise stated, the term "or" refers to the members listed individually and in any combination.
[0018] "Direct contact" is a configuration in which two components are in physical contact with one another with no intervening layers and / or no intervening materials between portions of the two components in contact.
[0019] "Ethylene / a-olefin copolymers" are interpolymers containing, as the only two monomer types, majority amounts of polymerized ethylene and a-olefin, based on the weight of the copolymer.
[0020] "Ethylene / α-olefin interpolymer" is an interpolymer that contains a majority amount of polymerized ethylene and at least one α-olefin, based on the weight of the interpolymer.
[0021] "Ethylene interpolymers" are interpolymers that contain, in polymerized form, ethylene in a majority amount, based on the weight of the interpolymer, and at least one comonomer.
[0022] "Ethylene-based polymers" are polymers that contain greater than 50 weight percent polymerized ethylene monomer, and optionally may contain at least one comonomer.
[0023] The term "film", including when referring to a "film layer" in a thicker article, unless explicitly specified with a thickness, includes any thin, flat extruded or cast article of generally uniform and uniform thickness, typically 25 microns to 1.25 millimeters (mm) or more. In a film, a "layer" can be very thin, such as in the case of a nanolayer or microlayer. As used herein, the term "sheet", unless explicitly specified with a thickness, includes any thin, flat extruded or cast article of generally uniform and uniform thickness greater than a "film".
[0024] "Glass" means a hard, brittle, transparent solid, such as used in windows, bottles or goggles, including, but not limited to, pure silicon dioxide (SiO2), soda-lime glass, borosilicate glass, sugar glass, mica flakes (Muscovy-glass), photovoltaic glass or aluminum oxynitride.
[0025] "Interpolymers" are polymers prepared by polymerizing at least two different types of monomers. The generic term interpolymer thus includes copolymers (used to refer to polymers prepared from two different types of monomers), terpolymers (used to refer to polymers prepared from three different types of monomers), and polymers prepared from more than three different types of monomers.
[0026] “Linear low density polyethylene” (“LLDPE”) is an ethylene-based polymer and comprises, in polymerized form, ethylene and C3-C 20 α-olefin comonomer, or C4-C8 α-olefin comonomer. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE.
[0027] "Low density polyethylene" ("LDPE") is an ethylene-based polymer and contains, in polymerized form, ethylene and optionally C3-C 20α-olefin comonomer, or C4-C8 α-olefin comonomer. LDPE is branched or heterogeneously branched polyethylene. LDPE has a relatively large number of long chain branches extending from the main polymer backbone. LDPE can be prepared using free radical initiators under high pressure, and the density is typically 0.915 g / cc to 0.940 g / cc.
[0028] An "olefin-based polymer" is a polymer that contains more than 50% polymerized olefin monomers (based on the total weight of the olefin-based polymer) and, optionally, may contain one or more comonomers. Non-limiting examples of olefin-based polymers include ethylene-based polymers and propylene-based polymers. The terms "olefin-based polymer" and "polyolefin" may be used interchangeably.
[0029] The terms "photovoltaic cell", "PV cell" and the like refer to a structure containing one or more photovoltaic effect materials of any of several inorganic or organic types. For example, commonly used photovoltaic effect materials include one or more of known photovoltaic effect materials, including but not limited to crystalline silicon, polycrystalline silicon, amorphous silicon, (di) copper indium gallium selenide (CIGS), copper indium selenide (CIS), cadmium telluride, gallium arsenide, dye-sensitized materials, and organic solar cell materials. Figure 1 As shown, PV cells are typically laminated and have at least one photoreactive surface that converts incident light into an electric current. Photovoltaic cells are well known to practitioners in the art and are typically packaged into photovoltaic modules to protect the cells and allow them to be used in their various application environments, typically in outdoor applications. Photovoltaic cells can be flexible or rigid in nature and contain photovoltaic effect materials and any protective coating surface materials applied in their production as well as appropriate wiring and electronic drive circuits.
[0030] "Photovoltaic module", "PV module" and the like terms refer to a structure containing PV cells. A PV module may also include a cover sheet, a front sealant film, a rear sealant film, and a back sheet, wherein the PV cells are sandwiched between the front sealant film and the rear sealant film. An exemplary PV module 2 is shown in FIG. Figure 1 Module 2 is a PV module having a plurality of layers 3, 4, 6, 7, and a plurality of layers 7. The PV module ... 7, and a plurality of layers 7. The PV module 2 is a PV module having a plurality of layers 3, 4, 6, 7, 7, 7, 7, 7, 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7 , 7
[0031] A "polymer" is a polymeric compound prepared by polymerizing monomers, whether of the same or a different type.The generic term "polymer" thus encompasses the term homopolymer (usually employed to refer to polymers prepared from only one type of monomer) and the term interpolymer.
[0032] Test Method
[0033] Density is measured according to ASTM D792 Method B. Results are expressed in grams (g) per cubic centimeter (g / cc or g / cm 3 ) in the form of records.
[0034] Flexural modulus (2% secant) is measured according to ASTM D790 and is reported in psi.
[0035] Glass Adhesion: The laminated sample was cut into three 1" wide samples (cutting the backsheet and film layers). The 180° peel test was used to measure the glass adhesion strength (maximum glass adhesion strength and average glass adhesion strength from 1" to 2" delamination). The test was performed on an Instron™ 5565 under controlled environmental conditions. At least three samples were tested to obtain an average value. The results are reported in Newtons per centimeter (N / cm).
[0036] Average transmittance: The transmittance of the compression molded films was determined using a LAMBDA 950 UV / Vis spectrophotometer (PerkinElmer) equipped with a 150 mm integrating sphere. At least three samples were tested and the average transmittance from 380 nm to 1100 nm was collected. The results are reported in percent (%).
[0037] Melt index (MI) measurements were performed according to ASTM D1238 at 190°C / 2.16 kilogram (kg) weight and reported in grams eluted per 10 minutes (g / 10 min).
[0038] Melt Crystallization and Glass Transition: Differential Scanning Calorimetry (DSC) can be used to measure the melting, crystallization, and glass transition behavior of polymers over a wide range of temperatures. For example, a TA Instruments Q1000 DSC equipped with a refrigerated cooling system (RCS) and an autosampler is used to perform this analysis. During the test, a nitrogen purge gas flow rate of 50 ml / min was used. Each sample was melt pressed into a film at about 175°C; the molten sample was then air cooled to room temperature (about 25°C). 3-10 mg of a 6 mm diameter specimen was extracted from the cooled polymer, weighed, placed in a light aluminum pan (approximately 50 mg), and crimped closed. Analysis was then performed to determine its thermal properties.
[0039] The thermal behavior of the sample is determined by ramping the sample temperature up and down to produce a heat flow versus temperature curve. First, the sample is quickly heated to 180°C and kept isothermal for 3 minutes to remove its thermal history. Next, the sample is cooled to -40°C at a cooling rate of 10°C / minute and kept isothermal at -40°C for 3 minutes. Then, the sample is heated to 180°C at a heating rate of 10°C / minute (this is the "second heating" ramp). Record the cooling and second heating curves. The cooling curve is analyzed by setting a baseline endpoint from the start of crystallization to -20°C. The heating curve is analyzed by setting a baseline endpoint from -20°C to the end of melting. The measured values are the extrapolated starting point of the melting Tm and the extrapolated starting point of the crystallization Tc. The heat of fusion (H f ) (in Joules per gram) and calculated % crystallinity using the following equation:
[0040] Crystallinity % = ((H f ) / 292J / g)x 100
[0041] Report the heat of fusion (H) from the second heating curve f ) and the peak melting temperature. The peak crystallization temperature is determined from the cooling curve.
[0042] The melting point Tm is determined from the DSC heating curve by first drawing a baseline between the start and end of the melting transition. A tangent line is then drawn to the data on the low temperature side of the melting peak. Where this tangent line intersects the baseline is the extrapolated onset of melting (Tm). This is as described in Bernhard Wunderlich, The Basis of Thermal Analysis, in Thermal Characterization of Polymeric Materials 92, 277-278 (Edith A. Turi, ed., 2nd ed., 1997).
[0043] The crystallization temperature Tc is determined from the DSC cooling curve as above, except that a tangent line is drawn on the high temperature side of the crystallization peak. Where this tangent line intersects the baseline is the extrapolated onset of crystallization (Tc).
[0044] The glass transition temperature, Tg, is determined from a DSC heating curve in which half of the sample has reached the liquid heat capacity, as described in Bernhard Wunderlich, Fundamentals of Thermal Analysis in Thermal Characterization of Polymeric Materials 92, 278-279 (Edith A. Turi, ed., 2nd ed., 1997). Base lines are drawn from below and above the glass transition region and extrapolated through the Tg region. The temperature at the midpoint between these base lines is the Tg.
[0045] Moving Die Rheometer (MDR): The MDR is loaded with approximately 4 grams of each cast film. The MDR is run at 150°C for 25 minutes. A time vs. torque curve is recorded for each sample at a given interval. The maximum torque applied by the MDR during the 25 minute test interval (MH) is recorded in deciNewton meters (dNm). The MH typically corresponds to the maximum torque applied at 25 minutes. The time required for the torque to reach x% of the MH (t x ) is recorded in minutes. x is a standardized measurement used to understand the curing kinetics of each resin. The time to reach 90% of MH (t 90 ).
[0046] Volume Resistivity: Volume resistivity was determined using a Keithley 6517B electrometer in combination with a Keithley 8009 test fixture. The Keithley Model 8009 test chamber was located within a forced air oven capable of operating at elevated temperatures (maximum temperature 60°C). The leakage current was recorded from the instrument via software and the volume resistivity (VR) was calculated using the following equation:
[0047]
[0048] Where ρ is the volume resistivity in ohm.cm, V is the applied voltage in volts, and A is the electrode contact area in cm 2 , I is the leakage current recorded after 10 minutes of applied voltage in amperes, and t is the thickness of the sample. The thickness of the compression molded film was measured before testing. Five points of the film were measured to obtain the average thickness for calculation. The test was performed at room temperature at 1000 volts. Two compression molded films were tested, and the VR recorded is the average of the two tests. The results are reported in ohm-centimeters (ohm.cm). DETAILED DESCRIPTION
[0049] The present disclosure provides a pelletized polymer composition consisting of: (A) an olefin-based polymer having a volume resistivity greater than 5.0*10 15 ohm.cm and (B) hydrophilic fumed silica. The pellets of the present disclosure are used to form compositions for sealant films, for example, for electronic devices such as photovoltaic modules.
[0050] The present disclosure also provides a composition, which is composed of the following: (A) an olefin-based polymer having a volume resistivity greater than 5.0*10 15ohm.cm, (B) hydrophilic fumed silica, (C) alkoxysilane, (D) organic peroxide, and optionally (E) a crosslinking aid. The composition of the present disclosure is used to produce a sealant film, such as for electronic devices, such as photovoltaic modules. In another embodiment, the present disclosure provides a film layer for electronic devices such as photovoltaic modules.
[0051] The present disclosure further provides a film layer for an electronic device such as a photovoltaic module, which is composed of: (A) an olefin-based polymer having a volume resistivity greater than 5.0*10 15 ohm.cm, (B) hydrophilic fumed silica, (C) alkoxysilane, (D) organic peroxide, and optionally (E) a crosslinking aid.
[0052] Olefin-based polymers
[0053] The olefin-based polymer is any olefin-based homopolymer (wherein the olefin is the only monomer) or olefin-based interpolymer where the olefin is the major monomer (i.e., the olefin-based interpolymer comprises greater than 50 weight percent of units derived from the olefin). In embodiments where the olefin-based polymer is an olefin-based interpolymer, the comonomers are different C 2-20 Straight chain, branched or cyclic alpha-olefins. For the purposes of this disclosure, ethylene is an alpha-olefin. C 2-20 Non-limiting examples of α-olefins include ethylene, propylene (propylene glycol), 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene.
[0054] In one embodiment, the olefin-based polymer is an ethylene-based polymer, i.e., an ethylene / α-olefin copolymer. Non-limiting examples of ethylene / α-olefin copolymers include copolymers of ethylene and C3-C8 α-olefins or C4-C8 α-olefins, such as ethylene / propylene copolymers, ethylene / butene copolymers, ethylene / 1-hexene copolymers, ethylene / 1-octene copolymers, linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), and combinations thereof.
[0055] The olefin-based polymer, or further the ethylene-based polymer, or further the ethylene / α-olefin copolymer may be random or blocky.
[0056] In one embodiment, the olefin-based polymer is a random olefin-based polymer, or further is a random ethylene-based copolymer, or further is a random ethylene / α-olefin copolymer.
[0057] The volume resistivity of olefin-based polymers is greater than 5.0*10 15In one embodiment, the volume resistivity of the olefin-based polymer is greater than 5.0*10 15 ohm.cm, or greater than 1.0*10 16 ohm.cm, or greater than 2.0*10 16 ohm.cm, or greater than 3.0*10 16 In one embodiment, the volume resistivity of the olefin-based polymer is greater than 5.0*10 15 ohm.cm, or greater than 1.0*10 16 ohm.cm, or greater than 2.0*10 16 ohm.cm, or greater than 3.0*10 16 ohm.cm to 4.0*10 16 ohm.cm, or 5.0*10 16 ohm.cm, or 7.0*10 16 ohm.cm, or 1.0*10 17 ohm.cm, or 5.0*10 17 ohm.cm, or 1.0*10 18 ohm.cm.
[0058] In one embodiment, the olefin-based polymer has a flexural modulus (2% secant) greater than, or equal to, 500 psi, or greater than, or equal to, 750 psi, or greater than, or equal to, 1000 psi to 2000 psi, or 3000 psi, or 3500 psi, or 4000 psi, or less than 6000 psi, as measured according to ASTM D790.
[0059] In one embodiment, the olefin-based polymer has a density from 0.850 g / cc, or 0.855 g / cc, or 0.860 g / cc, or 0.865 g / cc, or 0.880 g / cc to 0.885 g / cc, or 0.890 g / cc, or 0.900 g / cc, or 0.905 g / cc, or 0.910 g / cc, or 0.915 g / cc, or 0.920 g / cc, as measured according to ASTM D792, Method B.
[0060] In one embodiment, the olefin-based polymer has a melt index (MI) of 1 g / 10 min, or 5 g / 10 min, or 8 g / 10 min, or 10 g / 10 min to 20 g / 10 min, or 30 g / 10 min, or 35 g / 10 min, or 50 g / 10 min, or 75 g / 10 min, or 100 g / 10 min, as measured according to ASTM D1238.
[0061] In one embodiment, the olefin-based polymer has a melting point (Tm) of 55°C, or 60°C, or 75°C, or 90°C, or 95°C, or 100°C to 105°C, or 110°C, as measured using DSC.
[0062] In one embodiment, the olefin-based polymer has a glass transition temperature Tg of from -30°C, or -35°C to -40°C, or -45°C, or -50°C, or -60°, as measured using DSC.
[0063] In one embodiment, the olefin-based polymer is an ethylene / C3-C8 alpha-olefin copolymer having one, some or all of the following properties:
[0064] (i) Volume resistivity is greater than 5.0*10 15 ohm.cm, or greater than 1.0*10 16 ohm.cm, or greater than 2.0*10 16 ohm.cm, or greater than 3.0*10 16 ohm.cm to 4.0*10 16 ohm.cm, or 5.0*10 16 ohm.cm, or 7.0*10 16 ohm.cm, or 1.0*10 17 ohm.cm, or 5.0*10 17 ohm.cm, or 1.0*10 18 ohm.cm; and / or
[0065] (ii) a flexural modulus (2% secant) greater than or equal to 500 psi, or greater than or equal to 750 psi, or greater than or equal to 1000 psi to 2000 psi, or 3000 psi, or 3500 psi, or 4000 psi, or less than 6000 psi; and / or
[0066] (iii) a density of from 0.850 g / cc, or 0.855 g / cc, or 0.860 g / cc, or 0.865 g / cc, or 0.880 g / cc to 0.885 g / cc, or 0.890 g / cc, or 0.900 g / cc, or 0.905 g / cc, or 0.910 g / cc, or 0.915 g / cc, or 0.920 g / cc; and / or
[0067] (iv) a melt index (MI) of from 1 g / 10 min, or 5 g / 10 min, or 8 g / 10 min, or 10 g / 10 min to 20 g / 10 min, or 30 g / 10 min, or 35 g / 10 min, or 50 g / 10 min, or 75 g / 10 min, or 100 g / 10 min; and / or
[0068] (v) a melting point Tm of from 55°C, or 60°C, or 75°C, or 90°C, or 95°C, or 100°C to 105°C, or 110°C; and / or
[0069] (vi) The glass transition temperature Tg is from -30°C, or -35°C to -40°C, or -45°C, or -50°C, or -60°C.
[0070] In one embodiment, the ethylene / C3-C8 alpha-olefin copolymer has at least one, at least 2, at least 3, at least 4, at least 5, or all 6 of properties (i)-(vi).
[0071] In one embodiment, the ethylene / C3-C8 α-olefin copolymer has property (i) and at least one other property of properties (ii)-(vii).
[0072] In one embodiment, the ethylene / C3-C8 alpha-olefin copolymer is a copolymer of ethylene and a comonomer selected from octene, hexene, butene and propylene. In one embodiment, the ethylene / C3-C8 alpha-olefin copolymer is an ethylene / 1-octene copolymer.
[0073] Blends of any of the above olefin-based polymers may also be used, provided that the volume resistivity of the blend is greater than 5.0*10 15 The olefin-based polymer or blend thereof can be blended or diluted with one or more other polymers until the olefin-based polymer and the other polymers (i) are miscible with each other, (ii) the other polymers have little, if any, effect on the desired properties of the olefin-based polymer (i.e., optics and low modulus), and (iii) the olefin-based polymer content constitutes from greater than 50 weight percent, or 60 weight percent, or 70 weight percent, or 75 weight percent, or 80 weight percent to 90 weight percent, or 95 weight percent, or 98 weight percent, or 99 weight percent, or less than 100 weight percent of the blend, based on the total weight of the blend.
[0074] Volume resistivity greater than 5.0*10 15 The olefin-based polymer of ohm.cm may include two or more embodiments disclosed herein.
[0075] Hydrophilic fumed silica
[0076] Fumed silica is a type of synthetic amorphous silica. Synthetic amorphous silica (SAS) is a form of silicon dioxide (SiO2) that is intentionally manufactured, thereby distinguishing it from naturally occurring amorphous silica, such as diatomaceous earth. As a man-made product, SAS is almost 100% pure amorphous silica, while naturally occurring amorphous silica also contains crystalline forms of silicon dioxide. SAS can be made in two forms, with two different manufacturing practices: (1) wet process silica (including precipitated silica and silica gel), and (2) thermal process silica (including pyrogenic silica, also known as fumed silica). Therefore, fumed silica is SAS formed by a thermal process, rather than a wet process.
[0077] The thermal process for making fumed silica uses flame pyrolysis. Specifically, fumed silica is made from the flame pyrolysis of silicon tetrachloride or the vaporization of quartz sand in an electric arc at 3000°C. Exposure of microscopic droplets of amorphous silica to the electric arc causes the droplets to fuse into branched, chain-like, three-dimensional particles, which then further aggregate into tertiary particles. As a result, fumed silica particles have a lower bulk density and higher surface area than wet process silica particles (e.g., silica gel), and a higher purity than precipitated silica. Fumed silica particles are also non-porous, whereas wet process silica particles are porous.
[0078] Due to the thermal process used to make fumed silica particles, fumed silica particles are essentially hydrophilic unless they are specially treated. In order to form hydrophobic fumed silica particles, the fumed silica particles (hydrophilic) are chemically post-treated with a hydrophobic agent. A hydrophobic agent, such as an alkoxysilane, a silazane or a siloxane, covalently bonds to the oxide groups of the silica molecules on the fumed silica particles, thereby making the fumed silica particles hydrophobic. The term "hydrophilic fumed silica" as used herein is a non-porous fumed amorphous silica in particle form having reactive oxide groups of silica molecules on the surface of the fumed silica particles. In other words, hydrophilic fumed silica is a fumed amorphous silica that has not been chemically post-treated with a hydrophobic agent.
[0079] In one embodiment, the hydrophilic fumed silica has a particle size of less than 500 m 2 In one embodiment, the specific surface area (BET) of the hydrophilic fumed silica is from 120 m 2 / g, or 130m 2 / g, or 140m 2 / g, or 150m 2 / g, or 175m 2 / g to 190m 2 / g, or 200m2 / gm, or 210m 2 / g, or 220m 2 / g, or 230m 2 / g, or 250m 2 / g, or 275m 2 / g, or 300m 2 / g, or 310m 2 / g, or 320m 2 / g, or 340m 2 / g, or 360m 2 / g, or 380m 2 / g, or 410m 2 / g, or less than 500m 2 / g.
[0080] Non-limiting examples of commercially available hydrophilic fumed silica include 380, available from Evonik Industries.
[0081] The hydrophilic fumed silica may include two or more embodiments disclosed herein.
[0082] Alkoxysilane
[0083] Alkoxysilane is a silane compound containing at least one alkoxy group. Non-limiting examples of suitable alkoxysilanes include γ-chloropropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyl-tri-(β-methoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-ethoxy-cyclohexyl)ethyltrimethoxysilane, vinyltriacetoxysilane, γ-(methyl)acryloxy, propyltrimethoxysilane γ-glycidyloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-(trimethoxysilyl)propylmethacrylate.
[0084] In one embodiment, the alkoxysilane is selected from vinyl trimethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, or a combination thereof. In one embodiment, the silane compound is 3-(trimethoxysilyl)propyl methacrylate.
[0085] Organic peroxide
[0086] Non-limiting examples of suitable organic peroxides include dicumyl peroxide, dodecyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, di(tert-butyl peroxide), cumene hydroperoxide, 2,5-dimethyl-2,5-di(tert-butyl-peroxy)hexyne-3,2,-5-dimethyl-2,5-di(tert-butyl-peroxy)hexane, tert-butyl hydroperoxide, isopropyl percarbonate, α,α′-bis(tert-butylperoxy)diisopropylbenzene, t-butylperoxy-2-ethylhexyl-monocarbonate, 1,1-bis(tert-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethyl-2,5-dihydroxyperoxide, tert-butylperoxycumyl, α,α′-bis(tert-butylperoxy)-p-diisopropylbenzene, and the like.
[0087] Non-limiting examples of suitable commercially available organic peroxides include AkzoNobel's and ARKEMA TBEC.
[0088] Crosslinking aid
[0089] The auxiliary agent may be any one or a mixture of auxiliary agents including but not limited to esters, ethers, ketones, cyanurates, isocyanurates, phosphates, orthoformates, aliphatic or aromatic ethers containing at least 2 and preferably 3 unsaturated groups, such as allyl, vinyl or acrylate. The number of carbon atoms in the auxiliary agent may range from 9 to 40 or more, and is preferably from 9 to 20.
[0090] Specific examples of the auxiliary agent include, but are not limited to, triallyl cyanurate (TAC); triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione also known as triallyl isocyanurate (TAIC); hexaallyl melamine; triallyl phosphate (TAP); triallyl orthoformate; tetraallyloxyethane; triallyl benzene-1,3,5-tricarboxylate; diallyl phthalate; zinc dimethacrylate; ethoxylated bisphenol A dimethacrylate; methacrylate-terminated monomers with an average chain length of C14 or C1 5; pentaerythritol tetraacrylate; depentaerythritol pentaacrylate; pentaerythritol triacrylate; dimethylolpropane tetraacrylate; ethoxylated trimethylolpropane triacrylate; trimethylolpropane triacrylate; 2,4,6-triallyl-1,3,5-trione; 2,4-diphenyl-4-methyl-1-pentene; triallyl trimellitate (TATM); 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane (DVS); and alpha-methylstyrene dimer (AMSD), as well as other adjuvants described in USP 5,346,961 and 4,018,852.
[0091] In one embodiment, the one or more auxiliary agents are one or more of AMSD, TAP, TAC and TAIC.
[0092] Other additives
[0093] In addition to the hydrophilic fumed silica, the composition may also contain one or more additives. Non-limiting examples of suitable additives include other polymers, UV stabilizers and / or absorbers, antioxidants, scorch retardants, anti-slip agents, anti-blocking agents, pigments, fillers and combinations thereof. These additives may be provided in known amounts, and in some embodiments, may be added in the form of a masterbatch pre-blended in the amount of the polymer composition.
[0094] In one embodiment, the composition comprises a UV stabilizer. Non-limiting examples of suitable UV stabilizers include hindered phenols, phosphites, hindered amine light stabilizers (HALS), UV absorbers, hindered benzoates, and combinations of these. In one embodiment, HALS and hindered benzoates include, but are not limited to, UV 531 available from TCI; Cynergy A400, A430, and R350; Cyasorb UV-3529; Cyasorb UV-3346; Cyasorb UV-3583; Hostavin N30; Univil4050; Univin 5050; Chimassorb UV-119; Chimassorb 944LD; Tinuvin 622LD, etc. In one embodiment, the UV absorber comprises benzophenone, benzotriazole, triazine, and combinations of these, such as Tinuvin 328 or Cyasorb UV-1164.
[0095] In an embodiment, the composition comprises one or more other additives selected from processing stabilizers, antioxidants, anti-slip agents, pigments and fillers. In an embodiment, the antioxidant is selected from TCI's T770 Cyanox 2777; Irganox 1010; Irganox 1076; Irganox B215; Irganox B225; PEPQ; Weston 399; TNPP; Irgafos 168 and Devoerphos 9228.
[0096] Granulated polymer composition
[0097] The present disclosure provides a pelletized polymer composition, which comprises (A) a polymer having a volume resistivity greater than 5.0*10 15 The pelletized polymer composition is prepared by melt blending (A) a polymer having a volume resistivity greater than 5.0*10 15ohm.cm of an olefin-based polymer and (B) hydrophilic fumed silica, and pelletizing the blend to form.
[0098] In one embodiment, the pelletized polymer composition comprises 85 wt%, or 88 wt%, or 90 wt% to 92 wt%, or 95 wt% of the volume resistivity greater than 5.0*10 15 ohm.cm of an olefin-based polymer, and 5 wt%, or 8 wt% to 10 wt%, or 12 wt%, or 15 wt% hydrophilic fumed silica.
[0099] In one embodiment, the pelletized polymer composition may be referred to as a masterbatch.
[0100] The pellets of the present disclosure are used to form compositions as described below, such as sealant films for electronic devices such as photovoltaic modules.
[0101] Composition
[0102] The present disclosure provides a composition comprising (A) a volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymer, (B) hydrophilic fumed silica, (C) alkoxysilane, (D) organic peroxide, and optionally (E) a cross-linking aid.
[0103] In one embodiment, the composition comprises greater than 50 wt%, or 60 wt%, or 70 wt%, or 80 wt%, or 90 wt% to 95 wt%, or 98 wt%, or 99 wt%, or less than 100 wt% of a volume resistivity greater than 5.0*10 15 ohm.cm of an olefin-based polymer or a blend thereof. In one embodiment, based on the total weight of the resin composition, the composition comprises greater than 95.0 wt%, or 96.0 wt%, or 96.5 wt%, or 97.0 wt% to 97.5 wt%, or 98.0 wt%, or 98.5 wt% of a volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymers or blends thereof.
[0104] In one embodiment, the hydrophilic fumed silica is present in an amount from 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.5 wt% to 1.0 wt%, or 1.5 wt%, or 2.0 wt%, or 2.5 wt%, or 3.0 wt%, or 4.0 wt%, or 5.0 wt%, based on the total weight of the composition. In an embodiment, the hydrophilic fumed silica is present in an amount from 0.3 wt%, or 0.5 wt%, or 0.7 wt%, to 0.9 wt%, or 1.0 wt%, or 1.2 wt%, or 1.3 wt%, based on the total weight of the composition.
[0105] In an embodiment, the alkoxysilane is present in an amount of from 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.2 wt%, to 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, based on the total weight of the composition. In an embodiment, the alkoxysilane is present in an amount of from 0.10 wt%, or 0.15 wt%, or 0.20 wt%, to 0.25 wt%, or 0.30 wt%, or 0.35 wt%, based on the total weight of the composition.
[0106] Based on the total weight of the composition, the organic peroxide is present in the resin composition in an amount of from 0.1 wt %, or 0.5 wt %, or 0.75 wt % to 1.5 wt %, or 2 wt %, or 3 wt %, or 5 wt %. In an embodiment, based on the total weight of the composition, the organic peroxide is present in an amount of from 0.8 wt %, or 0.9 wt %, or 1.0 wt % to 1.1 wt %, or 1.2 wt %, or 1.3 wt %, or 1.5 wt %.
[0107] In one embodiment, based on the total weight of the composition, the amount of the adjuvant used is from 0 wt % or greater than 0 wt % (e.g., 0.01 wt %), or 0.1 wt %, or 0.2 wt % to 0.4 wt %, or 0.5 wt %, or 1.0 wt %, or 1.1 wt %, or 1.2 wt %, or 1.3 wt % or 1.5 wt %. In an embodiment, based on the total weight of the composition, the amount of the adjuvant used is from 0.30 wt %, or 0.40 wt %, or 0.50 wt % to 0.60 wt %, or 0.70 wt %, or 0.80 wt %.
[0108] In embodiments, the antioxidant is used and present in an amount from greater than 0 wt%, or 0.1 wt%, or 0.2 wt% to 0.3 wt%, or 0.5 wt%, or 1.0 wt%, or 3.0 wt%, based on the total weight of the composition.
[0109] In an embodiment, the UV stabilizer is used and present in an amount from greater than 0 wt%, or 0.01 wt%, or 0.05 wt% to 0.07 wt%, or 0.10 wt%, or 0.25 wt%, or 0.50 wt%, based on the total weight of the composition.
[0110] In one embodiment, the composition contains hydrophilic fumed silica to the exclusion of all other silicas, including hydrophobically treated fumed silica and micronized silica gel, and based on the total weight of the composition, the composition comprises: (A) from 90 wt% to less than 100 wt% of ethylene / C3-C8 α-olefin copolymer; (B) 0.01 wt% to 5.0 wt% of hydrophilic fumed silica; (C) 0.01 wt% to 2 wt% of an alkoxysilane selected from vinyltrimethoxysilane, (trimethoxysilyl)propylmethacrylate and combinations thereof; (D) 0.1 wt% to 5.0 wt% of an organic peroxide; (E) greater than 0 wt% to 1.5 wt% of a crosslinking aid.
[0111] In one embodiment, the composition contains hydrophilic fumed silica to the exclusion of all other silicas and to the exclusion of all other fillers.
[0112] In one embodiment, the composition is prepared by melt blending all components together. (A) Volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymer and (B) hydrophilic fumed silica are provided as a pelletized polymer composition or masterbatch, with a volume resistivity greater than 5.0*10 15 Additional olefin-based polymer pellets of ohm.cm are combined in appropriate proportions to produce a final concentration of hydrophilic fumed silica and then soaked in a mixture of the remaining ingredients of the composition, i.e., the alkoxysilane, organic peroxide and optional crosslinking aid, antioxidant and / or UV stabilizer.
[0113] Film
[0114] The present disclosure provides a film layer for an electronic device. The film layer is made of a composition comprising the following items: (A) a volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymer, (B) hydrophilic fumed silica, (C) alkoxysilane, (D) organic peroxide, and optionally (E) a crosslinking aid, such as disclosed herein.
[0115] The film layer is made by extruding the composition. The film layer made of the composition of the present disclosure can be prepared using various types of extruders, i.e. single screw or twin screw types. A typical extruder has a hopper at its upstream end and a die at its downstream end. Usually, the composition is provided in the form of a pelletized polymer composition that has been soaked in the necessary components. The pellets after soaking are fed to the hopper, and then melted and extruded at a temperature of 85°C, or 90°C, or 95°C, or 100°C to 105°C, or 110°C, or 115°C. In one embodiment, the rotor speed is from 20rpm, or 25rpm, or 30rpm to 35rpm, or 40rpm.
[0116] Melting and extruding the composition at temperatures generally below 120°C does not initiate crosslinking, curing or other reactions of the alkoxysilane. In particular, melting and extruding the composition at temperatures less than 120°C does not activate the peroxide and thus does not initiate crosslinking. It is desirable to avoid or limit crosslinking prior to lamination. Premature crosslinking and / or premature decomposition of the organic peroxide can result in reduced glass adhesion of the film layer. In other words, the film layer remains reactive until lamination, at which time crosslinking is initiated and the composition of the film layer becomes a reaction product comprising: (A) a volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymer, (B) hydrophilic fumed silica, (C) alkoxysilane, little if any residual (D) organic peroxide, and optionally (E) a crosslinking aid.
[0117] In one embodiment, the film layer is a single-layer structure and the thickness is from 100μm, or 150μm, or 200μm, or 250μm, or 300μm, or 350μm, or 400μm to 450μm, or 500μm, or 550μm, or 600μm, or 650μm, or 700μm, or 800μm.
[0118] The film layer comprises a composition, based on the total weight of the film layer, the composition comprises from greater than 50 weight %, or 60 weight %, or 70 weight %, or 80 weight %, or 90 weight % to 95 weight %, or 98 weight %, or 99 weight %, or less than 100 weight % of a volume resistivity greater than 5.0*10 15 ohm.cm of an olefin-based polymer or blend thereof. In one embodiment, the film layer comprises a composition comprising from greater than 95.0 wt%, or 96.0 wt%, or 96.5 wt%, or 97.0 wt% to 97.5 wt%, or 98.0 wt%, or 98.5 wt% of a volume resistivity greater than 5.0*10 15 ohm.cm olefin-based polymers or blends thereof.
[0119] Based on the total weight of the film layer, the hydrophilic fumed silica is present in an amount of from 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.5 wt% to 1.0 wt%, or 1.5 wt%, or 2.0 wt%, or 2.5 wt%, or 3.0 wt%, or 4.0 wt%, or 5.0 wt%. In an embodiment, based on the total weight of the film layer, the hydrophilic fumed silica is present in an amount of from 0.3 wt%, or 0.5 wt%, or 0.7 wt% to 0.9 wt%, or 1.0 wt%, or 1.2 wt%, or 1.3 wt%.
[0120] In an embodiment, the alkoxysilane is present in an amount of from 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.2 wt% to 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, based on the total weight of the film layer. In an embodiment, the alkoxysilane is present in an amount of from 0.15 wt%, or 0.20 wt%, or 0.25 wt% to 0.30 wt%, or 0.35 wt%, or 0.40 wt%, or 0.50 wt%, or 0.60 wt%, based on the total weight of the film layer.
[0121] Based on the total weight of the film layer, the amount of organic peroxide present in the film layer is from or 0.1 wt%, or 0.5 wt%, or 0.75 wt% to 1.5 wt%, or 2 wt%, or 3 wt%, or 5 wt%. In an embodiment, based on the total weight of the film layer, the amount of organic peroxide present in the film layer is from 0.8 wt%, or 0.9 wt%, or 1.0 wt% to 1.1 wt%, or 1.2 wt%, or 1.3 wt% or 1.5 wt%.
[0122] Based on the weight of the film layer, the amount of the auxiliary agent used is from 0 wt % or greater than 0 wt % (e.g., 0.01 wt %), or 0.1 wt %, or 0.2 wt % to 0.4 wt %, or 0.5 wt %, or 1.0 wt %, or 1.1 wt %, or 1.2 wt %, or 1.3 wt %, or 1.5 wt %. In one embodiment, based on the total weight of the film layer, the amount of the auxiliary agent used is from 0.30 wt %, or 0.40 wt %, or 0.50 wt % to 0.60 wt %, or 0.70 wt %, or 0.80 wt %.
[0123] In one embodiment, the antioxidant is used and present in an amount from greater than 0 wt%, or 0.1 wt%, or 0.2 wt% to 0.3 wt%, or 0.5 wt%, or 1.0 wt%, or 3.0 wt%, based on the total weight of the film layer.
[0124] In one embodiment, the UV stabilizer is used and present in an amount from greater than 0 wt%, or 0.01 wt%, or 0.05 wt% to 0.07 wt%, or 0.10 wt%, or 0.25 wt%, or 0.50 wt%, based on the total weight of the film layer.
[0125] In one embodiment, the film layer contains hydrophilic fumed silica to the exclusion of all other silicas, including hydrophobically treated fumed silica and micronized silica gel, and based on the total weight of the film layer, the film layer contains (A) from 90 wt% to less than 100 wt% of ethylene / C3-C8 α-olefin copolymer; (B) from 0.01 wt% to 5.0 wt% of hydrophilic fumed silica; (C) from 0.01 wt% to 2 wt% of an alkoxysilane selected from vinyltrimethoxysilane, (trimethoxysilyl)propylmethacrylate and combinations thereof; (D) from 0.1 wt% to 5.0 wt% of an organic peroxide; and (E) from greater than 0 wt% to 1.5 wt% of a crosslinking aid.
[0126] In one embodiment, the membrane layer contains hydrophilic fumed silica to the exclusion of all other silicas and all other fillers.
[0127] In one embodiment, the volume resistivity of the film layer is greater than or equal to 2.0*10 17 ohm.cm, or greater than or equal to 5.0*10 17 ohm.cm, or greater than or equal to 8.0*10 17 In one embodiment, the volume resistivity of the film layer is greater than or equal to 2.0*10 17 ohm.cm, or greater than or equal to 5.0*10 17 ohm.cm, or greater than or equal to 8.0*10 17 ohm.cm, or greater than or equal to 1.0*10 18 ohm.cm to 1.2*10 18 ohm.cm, or 1.4*10 18 ohm.cm, or 1.6*10 18 ohm.cm, or 2.0*10 18 ohm.cm, or 4.0*10 18 ohm.cm, or 6.0*10 18 ohm.cm.
[0128] In one embodiment, the film layer has an average transmittance greater than or equal to 89.00%. In one embodiment, the film layer has an average transmittance greater than or equal to 89.00%, or 90.00%, or 90.50%, or 90.75%, or 90.80%, or 90.85% to 90.90%, or 90.92%, or 90.94%, or 90.95%, or 91.00%, or 91.50%, or 91.75%, or 92.00%.
[0129] Film layer 1: In one embodiment, the film layer includes a composition comprising (A) from 90 wt % to 95 wt %, or 98 wt %, or 99 wt %, or less than 100 wt % of a volume resistivity greater than 5.0*10 15 ohm.cm of an olefin-based polymer, (B) from 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.5 wt% to 1.0 wt%, or 1.5 wt%, or 2.0 wt%, or 2.5 wt%, or 3.0 wt%, or 4.0 wt%, or 5.0 wt% of a hydrophilic fumed silica, (C) from 0.15 wt%, or 0.20 wt%, or 0.25 wt% to or 0.30 wt%, or 0.35 wt%, or 0.40 % by weight, or 0.50% by weight, or 0.60% by weight of alkoxysilane, (D) from 0.8% by weight, or 0.9% by weight, or 1.0% by weight to 1.1% by weight, or 1.2% by weight, or 1.3% by weight, or 1.5% by weight of an organic peroxide, and (E) from 0.00% by weight, or 0.01% by weight, or 0.30% by weight, or 0.40% by weight, or 0.50% by weight to 0.60% by weight, or 0.70% by weight, or 0.80% by weight of a crosslinking aid.
[0130] Film layer 2: In one embodiment, the film layer includes a composition, the composition including (A) from 90 wt % to 95 wt %, or 98 wt %, or 99 wt % or less than 100 wt % of a volume resistivity greater than 5.0*10 15ohm.cm of an ethylene / C3-C8 α-olefin copolymer, (B) from 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.5 wt% to 1.0 wt%, or 1.5 wt%, or 2.0 wt%, or 2.5 wt%, or 3.0 wt%, or 4.0 wt%, or 5.0 wt% of a hydrophilic fumed silica, (C) from 0.15 wt%, or 0.20 wt%, or 0.25 wt% to or 0.30 wt%, or 0.35 wt%, or 0 .40 wt%, or 0.50 wt%, or 0.60 wt% of alkoxysilane, (D) from 0.8 wt%, or 0.9 wt%, or 1.0 wt% to 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.5 wt% of organic peroxide, and (E) from 0.00 wt%, or 0.01 wt%, or 0.30 wt%, or 0.40 wt%, or 0.50 wt% to 0.60 wt%, or 0.70 wt%, or 0.80 wt% of a crosslinking aid.
[0131] Film layer 3: In one embodiment, the film layer comprises a composition comprising (A) from 90 wt % to 95 wt %, or 98 wt %, or 99 wt %, or less than 100 wt % of a volume resistivity greater than 5.0*10 15 ohm.cm of ethylene / C3-C8 α-olefin copolymer, (B) from 0.3 wt%, or 0.5 wt%, or 0.7 wt% to 0.9 wt%, or 1.0 wt%, or 1.2 wt%, or 1.3 wt% of hydrophilic fumed silica, (C) from 0.15 wt%, or 0.20 wt%, or 0.25 wt% to or 0.30 wt%, or 0.35 wt%, or 0.40 wt%, or 0.50 wt%, or 0.60 wt% of alkoxysilane, (D) from 0.8 wt%, or 0.9 wt%, or 1.0 wt% to 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.5 wt% of organic peroxide, and (E) from 0.30 wt%, or 0.40 wt%, or 0.50 wt% to 0.60 wt%, or 0.70 wt%, or 0.80 wt% of a crosslinking aid.
[0132] Film layer 4: In one embodiment, the film layer comprises a composition comprising (A) from greater than 95.0 wt%, or 96.0 wt%, or 96.5 wt%, or 97.0 wt% to 97.5 wt%, or 98.0 wt%, or 98.5 wt% of a volume resistivity greater than 5.0*10 15ohm.cm ethylene / C3-C8 alpha-olefin random copolymer, (B) from 0.3 wt%, or 0.5 wt%, or 0.7 wt% to 0.9 wt%, or 1.0 wt%, or 1.2 wt%, or 1.3 wt% of hydrophilic fumed silica, (C) from 0.15 wt%, or 0.20 wt%, or 0.25 wt% to or 0.30 wt%, or 0.35 wt%, or 0.40 wt%, or 0.50 wt%, or 0.60 wt% (D) from 0.8 wt%, or 0.9 wt%, or 1.0 wt% to 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.5 wt% of an organic peroxide, and (E) from 0.30 wt%, or 0.40 wt%, or 0.50 wt% to 0.60 wt%, or 0.70 wt%, or 0.80 wt% of a crosslinking aid.
[0133] In one embodiment, the film layer is consistent with film layer 1, film layer 2, film layer 3 or film layer 4 and has one, some or all three of the following properties:
[0134] (i) The volume resistivity is greater than or equal to 2.0*10 17 ohm.cm, or greater than or equal to 5.0*10 17 ohm.cm, or greater than or equal to 8.0*10 17 ohm.cm, or greater than or equal to 1.0*10 18 ohm.cm to 1.2*10 18 ohm.cm, or 1.4*10 18 ohm.cm, or 1.6*10 18 ohm.cm, or 2.0*10 18 ohm.cm, or 4.0*10 18 ohm.cm, or 6.0*10 18 ohm.cm; and / or
[0135] (ii) an average transmittance of from greater than or equal to 89.00%, or 90.00%, or 90.50%, or 90.75%, or 90.80%, or 90.85% to 90.90%, or 90.92%, or 90.94%, or 90.95%, or 91.00%, or 91.50%, or 91.75%, or 92.00%;
[0136] (iii) the thickness is from 100 μm, or 150 μm, or 200 μm, or 250 μm, or 300 μm, or 350 μm, or 400 μm to 450 μm, or 500 μm, or 550 μm, or 600 μm, or 650 μm, or 700 μm, or 800 μm.
[0137] In one embodiment, the film layer is consistent with Film Layer 1, Film Layer 2, Film Layer 3, or Film Layer 4 and has one, two, or all three properties (i)-(iii).
[0138] A film layer may comprise two or more embodiments described herein.
[0139] PV modules
[0140] The compositions of the present disclosure are used to construct electronic device modules, in particular sealant films for constructing electronic device modules. The sealant film is used as one or more "skins" of the electronic device, i.e., applied to one or both surfaces of the electronic device, for example, as a front sealant film or a rear sealant film, or as both a front sealant film and a rear sealant film, such as where the electronic device is completely encapsulated within the material.
[0141] A "photovoltaic module" or "PV module" is a laminated structure and comprises the following layer components assembled into the final module structure, such as Figure 1 As shown:
[0142] 1. Light receiving and transmitting layer;
[0143] 2. Front sealant film layer (transparent);
[0144] 3. One or more photovoltaic cells (or "PV cells");
[0145] 4. A rear sealant film layer; and
[0146] 5. Back panel.
[0147] In one embodiment, the light receiving and transmitting layer is glass, acrylic resin, polycarbonate, polyester or fluorine-containing resin. In one embodiment, the light receiving and transmitting layer is glass.
[0148] The number of photovoltaic cells in a given photovoltaic module will vary depending on the nature and use of the electronic device utilizing the photovoltaic module.In one embodiment, at least one photovoltaic cell is in direct contact with the front and rear encapsulant film layers.
[0149] In one embodiment, the backplane is a polymer backplane or a glass backplane.
[0150] The layers (1) to (5) of the PV module having the above-mentioned laminated structure are bonded by lamination. By lamination, the top sheet is in direct contact with the front sealant film layer, and the back sheet is in direct contact with the rear sealant film layer. The photovoltaic cell is fixed between the front sealant film layer and the rear sealant film layer and is in direct contact with them. Therefore, parts of the front sealant film and the rear sealant film are in direct contact with each other.
[0151] In one embodiment, the present disclosure provides a PV module. The PV module comprises a film layer of the present disclosure. The film layer of the present disclosure can be a front sealant film layer, a rear sealant film layer, a back sheet film layer, and combinations thereof. In other embodiments, the film layer can be the entire film, or one or more discrete sub-layers of the film.
[0152] In one embodiment, the film layer is a front sealant film layer. The front sealant film layer is in direct contact with the photovoltaic cell. In another embodiment, the front sealant film layer is a single layer structure and has a thickness of from 100 μm, or 150 μm, or 200 μm, or 250 μm, or 300 μm, or 350 μm, or 400 μm to 450 μm, or 500 μm, or 550 μm, or 600 μm, or 650 μm, or 700 μm, or 800 μm.
[0153] In one embodiment, the film layer is a rear sealant film layer. The rear sealant film layer is in direct contact with the photovoltaic cell. In another embodiment, the rear sealant film layer is a single layer structure and has a thickness of from 100 μm, or 150 μm, or 200 μm, or 250 μm, or 300 μm, or 350 μm, or 400 μm to 450 μm, or 500 μm, or 550 μm, or 600 μm, or 650 μm, or 700 μm, or 800 μm.
[0154] In one embodiment, the front sealant film layer and the rear sealant film layer are both film layers as disclosed herein. Each of the front sealant film layer and the rear sealant film layer directly contacts the photovoltaic cell. A portion of the front sealant film layer also directly contacts a portion of the rear sealant film layer. The front sealant film layer and the rear sealant film layer can be as previously described.
[0155] In one embodiment, a film layer comprising a composition of the present disclosure is applied to an electronic device by one or more lamination techniques. By lamination, a cover sheet is in direct contact with a first surface of the sealant film layer, and the electronic device is in direct contact with a second surface of the sealant film layer. In another embodiment, the cover sheet is in direct contact with a first surface of the front sealant film layer, a back sheet is in direct contact with a second surface of the rear sealant film layer, and the electronic device is fixed between and in direct contact with the second surface of the front sealant film layer and the first surface of the rear sealant film layer.
[0156] In one embodiment, the lamination temperature is sufficient to activate the organic peroxide and crosslink the composition, i.e., for example, the composition disclosed herein comprising (A) a volume resistivity greater than 5.0*10 15 The composition of (A) an olefin-based polymer of ohm.cm, (B) a hydrophilic fumed silica, (C) an alkoxysilane, (D) an organic peroxide, and optionally (E) a crosslinking aid remains reactive prior to lamination when crosslinking occurs. The alkoxysilane also interacts with the surface of the cover sheet to increase the adhesion between the sealant film layer and the cover sheet. After lamination, the composition is a reaction product of a composition comprising (A) a volume resistivity greater than 5.0*10 15 (B) hydrophilic fumed silica, (C) alkoxysilane, (D) organic peroxide, and optionally (E) crosslinking aid. That is, during lamination, at least a portion of the peroxide is consumed and the olefin-based polymer is crosslinked by reacting with the alkoxysilane. Therefore, the term "sealant film layer" used herein refers to the film layer of the electronic device after lamination, which is a silane crosslinked film layer.
[0157] In one embodiment, the lamination temperature for producing electronic devices is from 130° C., or 135° C., or 140° C., or 145° C. to 150° C., or 155° C., or 160° C. In one embodiment, the lamination time is from 8 minutes, or 10 minutes, or 12 minutes, or 15 minutes to 18 minutes, or 20 minutes, or 22 minutes, or 25 minutes.
[0158] In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a glass adhesion of greater than 100 N / cm, or greater than 110 N / cm, or greater than 130 N / cm, or greater than 140 N / cm, or greater than 150 N / cm, or greater than 160 N / cm. In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a glass adhesion of greater than 100 N / cm, or greater than 110 N / cm, or greater than 120 N / cm to 130 N / cm, or 140 N / cm, or 150 N / cm, or 160 N / cm, or 165 N / cm, or 170 N / cm, or 180 N / cm, or 190 N / cm. In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a glass adhesion of greater than 160 N / cm, or greater than 165 N / cm, or greater than 170 N / cm to 180 N / cm, or 190 N / cm.
[0159] In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a MH greater than 3.1 dNm. In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a maximum torque (MH) from greater than 3.10 dNm, or 3.15 dNm to 3.20 dNm, or 3.25 dNm, or 3.50 dNm.
[0160] In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a t90 of less than 13.000 minutes. In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a t90 of less than 13.000 minutes, or less than 12.500 minutes, or less than 12.000 minutes, or less than 11.750 minutes, or less than 11.500 minutes, or less than 11.250 minutes to 11.000 minutes, or 10.900 minutes, or 10.800 minutes, or 10.750 minutes, or 10.500 minutes, or 10.250 minutes.
[0161] In one embodiment, the electronic device of the present disclosure includes a 17 ohm.cm, or greater than or equal to 5.0*10 17 ohm.cm, or greater than or equal to 8.0*10 17 ohm.cm. In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having a volume resistivity greater than or equal to 2.0*10 17 ohm.cm, or greater than or equal to 5.0*10 17 ohm.cm, or greater than or equal to 8.0*10 17 ohm.cm, or 1.0*10 18 ohm.cm to 1.2*10 18 ohm.cm, or 1.4*10 18 ohm.cm, or 1.6*10 18 ohm.cm, or 2.0*10 18 ohm.cm, or 4.0*10 18 ohm.cm, or 6.0*10 18 The volume resistivity of the sealant film layer is ohm.cm.
[0162] In one embodiment, the electronic device of the present disclosure comprises a sealant film layer having an average transmittance greater than or equal to 89.00%. In one embodiment, the electronic device of the present disclosure comprises a sealant film having an average transmittance greater than or equal to 89.00%, or 90.00%, or 90.50%, or 90.75%, or 90.80%, or 90.85% to 90.90%, or 90.92%, or 90.94%, or 90.95%, or 91.00%, or 91.50%, or 91.75%, or 92.00%.
[0163] In one embodiment, the electronic device of the present invention includes a sealant film layer as a single-layer structure, whose thickness is from 100μm, or 150μm, or 200μm, or 250μm, or 300μm, or 350μm, or 400μm to 450μm, or 500μm, or 550μm, or 600μm, or 650μm, or 700μm, or 800μm.
[0164] In one embodiment, the film layer according to film layer 1, film layer 2, film layer 3 or film layer 4 is used to form an electronic device. Therefore, the resulting electronic device comprises a sealant film layer: sealant film layer 1, sealant film layer 2, sealant film layer 3, or sealant film layer 4, which are silane-crosslinked laminated products of film layer 1, film layer 2, film layer 3 or film layer 4, respectively.
[0165] In one embodiment, the electronic device of the present disclosure includes a sealant film layer according to sealant film layer 1, sealant film layer 2, sealant film layer 3, or sealant film layer 4, which has one, some, or all of the following properties:
[0166] (i) glass adhesion from greater than 160 N / cm, or greater than 165 N / cm, or greater than 170 N / cm to 180 N / cm, or 190 N / cm, or 195 N / cm, or 200 N / cm; and / or
[0167] (ii) a MH from greater than 3.1 dNm, or 3.15 dNm to 3.20 dNm, or 3.25 dNm, or 3.5 dNm; and / or
[0168] (iii) a t90 of from less than 13.000 minutes, or less than 12.500 minutes, or less than 12.000 minutes, or less than 11.750 minutes, or less than 11.500 minutes, or less than 11.250 minutes to 11.000 minutes, or 10.900 minutes, or 10.800 minutes, or 10.750 minutes, or 10.500 minutes, or 10.250 minutes.
[0169] (iv) from greater than or equal to 2.0*10 17ohm.cm, or greater than or equal to 5.0*10 17 ohm.cm, or greater than or equal to 8.0*10 17 ohm.cm, or greater than or equal to 1.0*10 18 ohm.cm to 1.2*10 18 ohm.cm, or 1.4*10 18 ohm.cm, or 1.6*10 18 ohm.cm, or 2.0*10 18 ohm.cm, or 4.0*10 18 ohm.cm, or 6.0*10 18 Volume resistivity of ohm.cm; and / or
[0170] (v) an average transmittance of from greater than or equal to 89.00%, or 90.00%, or 90.50%, or 90.75%, or 90.80%, or 90.85% to 90.90%, or 90.92%, or 90.94%, or 90.95%, or 91.00%, or 91.50%, or 91.75%, or 92.00%; and / or
[0171] (vi) a thickness of from 100 μm, or 150 μm, or 200 μm, or 250 μm, or 300 μm, or 350 μm, or 400 μm to 450 μm, or 500 μm, or 550 μm, or 600 μm, or 650 μm, or 700 μm, or 800 μm.
[0172] In one embodiment, the electronic device of the present disclosure comprises a sealant film layer according to sealant film layer 1, sealant film layer 2, sealant film layer 3, or sealant film layer 4, which has at least 2, at least 3, at least 4, at least 5, or all 6 of properties (i)-(vi).
[0173] Some embodiments of the present disclosure will now be described in detail in the following examples.
[0174] Examples
[0175] Material
[0176] Table 1: Materials used and their properties
[0177]
[0178] **Compare
[0179] Sample preparation
[0180] Ethylene / octene copolymer pellets were fed into a Brabender mixer at a temperature of 130°C and a rotor speed of 10 rpm. Various fumed silicas were then added according to the formulations provided in Table 2 below. Final mixing was performed at 130°C and a rotor speed of 80 rpm for 5 minutes. The resulting compound was collected and cut into small pieces.
[0181] Small pieces of ethylene / octene copolymer / silica (or only ethylene / octene copolymer if no silica is added) are fed into the hopper of a Brabender single extruder. The small pieces are extruded into melt strands at 110°C and a screw speed of 25 rpm. The melt strands are fed to a Brabender pelletizer to prepare pellets.
[0182] Alkoxysilane, peroxide, auxiliaries and any additional additives, such as UV stabilizers and antioxidants, are weighed and mixed in a sealable plastic bottle according to Table 2 below. The pellets are weighed and added to the plastic bottle according to Table 2. To ensure uniform distribution and complete soaking, the plastic bottle is first tumbled for 1 minute and then placed on a running roller and further homogenized in an oven at 40°C for 15-20 hours before use.
[0183] Membrane preparation
[0184] After soaking, the pellets were fed into a Brabender single screw mixer at a rotor speed of 30 rpm at 105° C. Films with a thickness of approximately 0.5 mm were prepared and stored in sealed aluminum foil bags for testing.
[0185] Compression molding
[0186] The cast film was compression molded into a 0.5 mm film. The sample was placed in the mold, preheated to 120°C for 5 minutes, and then degassed by 8 pressure loading / releasing cycles. The degassed sample was then pressurized at 150°C for 15 minutes and cooled to room temperature. The compression molded sheets were used for volume resistivity and transmittance testing.
[0187] laminated
[0188] The 4" x 6" glass plate was cleaned with water and dried before use. The backsheet was cut into four 6-inch squares. The film sample was cut into sheets to fit the size of the glass and backsheet. The backsheet, film sample, and glass were laminated together to form a backsheet / film sample / glass structure, and then laminated on a PENERGY L036 laminator at 150°C for 20 minutes (4 minutes vacuum and 16 minutes press). The laminated samples were used for glass adhesion testing.
[0189] Table 2: Sample formulation and properties
[0190]
[0191] CS = comparative sample; IE = inventive example
[0192] As shown in CS1-4, in the case of a VR less than 5.0*10 15 Adding hydrophilic fumed silica to a resin composition based on ethylene / octene copolymer deteriorates the VR of the composition. Comparative Sample 1 is composed of a resin composition having a VR less than 5.0*10 15 ohm.cm of pure resin (no additives). Comparative sample 2 is made of a film containing VR less than 5.0*10 15 ohm.cm of ethylene / octene copolymer and additives but without silica. The addition of additives other than silica has minimal effect on the VR of the composition (from 1.0*10 of the composition of the pure resin for CS1). 15 ohm.cm to 1.1*10 for CS2 15 ohm.cm). As shown in CS3, the addition of hydrophilic fumed silica reduces (deteriorates) the VR to less than 5.0*10 15 ohm.cm VR of the resin composition of ethylene / octene copolymer. CS3 comprises hydrophilic fumed silica and having a VR less than 5.0*10 15 ohm.cm, and has an 8.7*10 14 CS4 shows that the addition of UV stabilizer to the hydrophilic fumed silica-containing resin composition of CS3 slightly improves the VR of the resin composition as expected, but the improvement is less than one order of magnitude, i.e., from 1.0*10 15 ohm.cm to 6.9*10 15 ohm.cm.
[0193] Comparative sample 5 is composed of a sample having a value greater than 5.0*10 15 ohm.cm VR pure resin (no additives) film layer. Comparative sample 6 is a film layer made of VR with a value greater than 5.0*10 15 The applicant surprisingly found that the base resin in the olefin-based polymer has a VR greater than 5.0*10 15 ohm.cm, the inclusion of hydrophilic fumed silica resulted in a significant improvement in VR. 17 Compared with CS5-6, IE1 has a VR value of greater than 2.0*10 17ohm.cm, and further has a VR greater than 8.0*10 17 ohm.cm VR. In particular, the VR values of CS5 and CS6 are 4.0*10 16 ohm.cm and 1.8*10 17 ohm.cm, while the VR value of IE1 is 1.06*10 18 ohm.cm.
[0194] In addition, the applicant surprisingly found that in the case of a 15 The inclusion of hydrophilic fumed silica in films of ethylene / octene copolymers having a VR of 1.0 ohm.cm resulted in films having improved VR (i.e., VR greater than 2.0*10 17 ohm.cm) and ideal glass adhesion (i.e., glass adhesion greater than 100 N / cm). CS6 (cured resin, no silica) has a glass adhesion of 140.55 N / cm and poor VR (1.8*10 17 ohm.cm). The inclusion of hydrophilic fumed silica has little effect on glass adhesion compared to a cured resin without silica (CS6). Each of IE1-2 has a glass adhesion greater than 100 N / cm, and even greater than 120 N / cm. In particular, the glass adhesion of IE1-2 ranges from 164.1 N / cm (IE1) to 192.5 N / cm (IE2).
[0195] As shown in the comparison between CS1-6 and IE1-4, in the case of VR greater than 5.0*10 15 The inclusion of hydrophilic fumed silica in a film composed of an olefin-based polymer resin composition of ohm.cm results in a film having an improved VR (i.e., a VR greater than 2.0*10 17 ohm.cm) and a combination of ideal glass adhesion (i.e., glass adhesion greater than 100 N / cm).
[0196] It is particularly intended that the present invention is not limited to the embodiments and descriptions contained herein, but rather encompasses modifications of those embodiments, including parts of the embodiments and combinations of elements of different embodiments occurring within the scope of the appended claims.
[0197] In summary, the present invention includes but is not limited to the following items:
[0198] 1. A composition comprising:
[0199] (A) an olefin-based polymer having a molecular weight greater than 5.0*10 15 Volume resistivity in ohm.cm;
[0200] (B) hydrophilic fumed silica;
[0201] (C) alkoxysilane;
[0202] (D) organic peroxides; and
[0203] (E) from 0% to 1.5% by weight of a crosslinking aid.
[0204] 2. The composition according to claim 1, comprising, based on the total weight of the composition:
[0205] (A) from 90 wt% to less than 100 wt% of an ethylene / α-olefin copolymer;
[0206] (B) from 0.01 wt % to 2 wt % of an alkoxysilane selected from the group consisting of vinyltrimethoxysilane, (trimethoxysilyl)propylmethacrylate, and combinations thereof;
[0207] (C) from 0.01 wt % to 5.0 wt % of said hydrophilic fumed silica;
[0208] (D) from 0.1 wt % to 5.0 wt % of said organic peroxide; and
[0209] (E) from greater than 0 wt % to 1.5 wt % of the crosslinking aid.
[0210] 3. The composition of clause 2, wherein the olefin-based polymer has a flexural modulus (2% secant) from greater than or equal to 500 psi to less than 6000 psi.
[0211] 4. A film layer comprising a composition, the composition comprising:
[0212] (A) an olefin-based polymer having a molecular weight greater than 5.0*10 15 Volume resistivity in ohm.cm;
[0213] (B) hydrophilic fumed silica;
[0214] (C) alkoxysilane;
[0215] (D) organic peroxides; and
[0216] (E) from 0% to 1.5% by weight of a crosslinking aid,
[0217] The film layer has a thickness ranging from 5.0*10 17 ohm.cm to 6.0*10 18 Volume resistivity of ohm.cm.
[0218] 5. The film layer according to claim 4, wherein the composition comprises, based on the total weight of the composition:
[0219] (A) from 90 wt% to less than 100 wt% of an ethylene / α-olefin copolymer;
[0220] (B) from 0.01 wt % to 2 wt % of said alkoxysilane;
[0221] (C) from 0.01 wt % to 5.0 wt % of said hydrophilic fumed silica;
[0222] (D) from 0.1 wt % to 5.0 wt % of said organic peroxide; and
[0223] (E) from greater than 0 wt % to 1.5 wt % of the crosslinking aid.
[0224] 6. The film layer of any one of items 4 to 5, wherein the alkoxysilane is selected from the group consisting of vinyltrimethoxysilane, (trimethoxysilyl)propyl methacrylate, and combinations thereof.
[0225] 7. The film layer according to any one of items 4 to 6, wherein the film layer has a glass adhesion of from 160 N / cm to 190 N / cm.
[0226] 8. The film layer of any one of items 4 to 7, wherein the film layer has a t90 of from less than 11.250 minutes to 10.250 minutes.
[0227] 9. A photovoltaic module, comprising:
[0228] Photovoltaic cells; and
[0229] A film layer composed of a composition which is a reaction product of a composition comprising:
[0230] (A) an olefin-based polymer having a molecular weight greater than 5.0*10 15 Volume resistivity in ohm.cm;
[0231] (B) hydrophilic fumed silica;
[0232] (C) alkoxysilane;
[0233] (D) organic peroxides; and
[0234] (E) from 0% to 1.5% by weight of a crosslinking aid,
[0235] The film layer has a thickness ranging from 5.0*10 17ohm.cm to 6.0*10 18 Volume resistivity of ohm.cm.
[0236] 10. The photovoltaic module according to item 9, wherein the composition comprises, based on the total weight of the composition,
[0237] (A) from 90 wt% to less than 100 wt% of an ethylene / α-olefin copolymer;
[0238] (B) from 0.01 wt % to 2 wt % of said alkoxysilane;
[0239] (C) from 0.01 wt % to 5.0 wt % of said hydrophilic fumed silica;
[0240] (D) from 0.1 wt % to 5.0 wt % of said organic peroxide; and
[0241] (E) from greater than 0 wt % to 1.5 wt % of the crosslinking aid.
[0242] 11. The photovoltaic module of any one of items 9 to 10, wherein the olefin-based polymer is an ethylene / C3-C8 α-olefin copolymer having a flexural modulus (2% secant) from less than 6000 psi to greater than or equal to 500 psi.
[0243] 12. The photovoltaic module according to any one of items 9 to 11, wherein the alkoxysilane is selected from the group consisting of vinyltrimethoxysilane, (trimethoxysilyl)propyl methacrylate, and combinations thereof.
[0244] 13. The photovoltaic module according to any one of items 9 to 12, wherein the film layer has a glass adhesion of from 160 N / cm to 190 N / cm.
[0245] 14. The photovoltaic module of clause 13, wherein the film layer is a front encapsulant film layer and has an average transmittance of from greater than or equal to 90.00% to 92.00%.
[0246] 15. The photovoltaic module according to any one of items 9 to 14, wherein the film layer has a t90 of from less than 11.250 minutes to 10.250 minutes.
Claims
1. A composition comprising: (A) an olefin-based polymer having a molecular weight greater than 5.0*10 15 Volume resistivity in ohm.cm; (B) hydrophilic fumed silica; (C) alkoxysilane; (D) organic peroxides; and (E) from 0% to 1.5% by weight of a crosslinking aid.
2. The composition according to claim 1, comprising, based on the total weight of the composition: (A) from 90 wt% to less than 100 wt% of an ethylene / α-olefin copolymer; (B) from 0.01 wt % to 2 wt % of an alkoxysilane selected from the group consisting of vinyltrimethoxysilane, (trimethoxysilyl)propylmethacrylate, and combinations thereof; (C) from 0.01 wt % to 5.0 wt % of said hydrophilic fumed silica; (D) from 0.1 wt % to 5.0 wt % of said organic peroxide; and (E) from greater than 0 wt % to 1.5 wt % of the crosslinking aid.
3. The composition of claim 2, wherein the olefin-based polymer has a flexural modulus (2% secant) from greater than or equal to 500 psi to less than 6000 psi.
4. A film layer comprising a composition, the composition comprising: (A) an olefin-based polymer having a molecular weight greater than 5.0*10 15 Volume resistivity in ohm.cm; (B) hydrophilic fumed silica; (C) alkoxysilane; (D) organic peroxides; and (E) from 0% to 1.5% by weight of a crosslinking aid, The film layer has a thickness ranging from 5.0*10 17 ohm.cm to 6.0*10 18 Volume resistivity of ohm.cm.
5. The film layer according to claim 4, wherein the composition comprises, based on the total weight of the composition: (A) from 90 wt% to less than 100 wt% of an ethylene / α-olefin copolymer; (B) from 0.01 wt % to 2 wt % of said alkoxysilane; (C) from 0.01 wt % to 5.0 wt % of said hydrophilic fumed silica; (D) from 0.1 wt % to 5.0 wt % of said organic peroxide; and (E) from greater than 0 wt % to 1.5 wt % of the crosslinking aid.
6. The film layer of any one of claims 4 to 5, wherein the alkoxysilane is selected from the group consisting of vinyltrimethoxysilane, (trimethoxysilyl)propyl methacrylate, and combinations thereof.
7. The film layer according to any one of claims 4 to 6, wherein the film layer has a glass adhesion of from 160 N / cm to 190 N / cm.
8. The film layer of any one of claims 4 to 7, wherein the film layer has a t90 of from less than 11.250 minutes to 10.250 minutes.
9. A photovoltaic module, comprising: Photovoltaic cells; as well as A film layer composed of a composition which is a reaction product of a composition comprising: (A) an olefin-based polymer having a molecular weight greater than 5.0*10 15 Volume resistivity in ohm.cm; (B) hydrophilic fumed silica; (C) alkoxysilane; (D) organic peroxides; and (E) from 0% to 1.5% by weight of a crosslinking aid, The film layer has a thickness ranging from 5.0*10 17 ohm.cm to 6.0*10 18 Volume resistivity of ohm.cm.
10. The photovoltaic module according to claim 9, wherein the composition comprises, based on the total weight of the composition, (A) from 90 wt% to less than 100 wt% of an ethylene / α-olefin copolymer; (B) from 0.01 wt % to 2 wt % of said alkoxysilane; (C) from 0.01 wt % to 5.0 wt % of said hydrophilic fumed silica; (D) from 0.1 wt % to 5.0 wt % of said organic peroxide; and (E) from greater than 0 wt % to 1.5 wt % of the crosslinking aid.
11. The photovoltaic module of any one of claims 9 to 10, wherein the olefin-based polymer is an ethylene / C3-C8 alpha-olefin copolymer having a flexural modulus (2% secant) from less than 6000 psi to greater than or equal to 500 psi.
12. The photovoltaic module of any one of claims 9 to 11, wherein the alkoxysilane is selected from the group consisting of vinyltrimethoxysilane, (trimethoxysilyl)propyl methacrylate, and combinations thereof.
13. The photovoltaic module according to any one of claims 9 to 12, wherein the film layer has a glass adhesion of from 160 N / cm to 190 N / cm.
14. The photovoltaic module of claim 13, wherein the film layer is a front encapsulant film layer and has an average transmittance from greater than or equal to 90.00% to 92.00%.
15. The photovoltaic module of any one of claims 9 to 14, wherein the film layer has a t90 of from less than 11.250 minutes to 10.250 minutes.
Citation Information
Patent Citations
Composition with triallyl compounds and process for avoiding scorching of ethylene polymer composition
US4018852A